2022
DOI: 10.3389/fpls.2022.952758
|View full text |Cite
|
Sign up to set email alerts
|

SlMYC2 mediates stomatal movement in response to drought stress by repressing SlCHS1 expression

Abstract: Drought stress limits plant development and reproduction. Multiple mechanisms in plants are activated to respond to stress. The MYC2 transcription factor is a core regulator of the jasmonate (JA) pathway and plays a vital role in the crosstalk between abscisic acid (ABA) and JA. In this study, we found that SlMYC2 responded to drought stress and regulated stomatal aperture in tomato (Solanum lycopersicum). Overexpression of SlMYC2 repressed SlCHS1 expression and decreased the flavonol content, increased the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…We identified 19 DEGs that increased and 17 DEGs that decreased under both control and stress conditions (Figure 2a; Table S6). Of these 36 DEGs, we found the negative regulator of ABA signaling, protein phosphatases type 2C ( SlPP2C1 , Solyc03g096670), and one chalcone synthase1 ( SlCHS1 , Solyc09g091510) that played a negative role in drought/ABA‐induced stomatal closure (Watkins et al., 2014; Xu et al., 2022). The stress‐induced elevated expression (FPKM Drought versus FPKM Control ) of these two negative regulators ( SlPP2C1 and SlCHS1 ) was inhibited by the elevation of endogenous JA levels (Figure 2b), suggesting that JA regulated stomatal movements by transcriptionally hindering the negative modulators related to the ABA signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 19 DEGs that increased and 17 DEGs that decreased under both control and stress conditions (Figure 2a; Table S6). Of these 36 DEGs, we found the negative regulator of ABA signaling, protein phosphatases type 2C ( SlPP2C1 , Solyc03g096670), and one chalcone synthase1 ( SlCHS1 , Solyc09g091510) that played a negative role in drought/ABA‐induced stomatal closure (Watkins et al., 2014; Xu et al., 2022). The stress‐induced elevated expression (FPKM Drought versus FPKM Control ) of these two negative regulators ( SlPP2C1 and SlCHS1 ) was inhibited by the elevation of endogenous JA levels (Figure 2b), suggesting that JA regulated stomatal movements by transcriptionally hindering the negative modulators related to the ABA signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…MYC2 plays a crucial role in the dehydration stress memory response (Avramova, 2019). Xu et al (2022) recently reported that the MYC2 gene was induced by drought stress and played a positive role in regulating stomatal closure in tomato. The expression of MYC2 was also induced by MeJA treatment (Figure S5).…”
Section: Myc2 Regulated Candidate Genes During the Drought Stress Res...mentioning
confidence: 99%
See 2 more Smart Citations
“…In drought-stressed plants, ABA is a major phytohormone involved in regulating stomatal aperture [54]. According to the reports from Populus euphratica [55], Oryza sativa [56] and Solanum lycopersicum [57], plants increased drought tolerance by modulating stomatal closing. Our results showed that in comparison with WT, AgMYB5 transgenic lines inhibited water loss rate by reducing the degree of stomatal aperture, thereby enhanced drought tolerance.…”
Section: Discussionmentioning
confidence: 99%